Study of pathogenic bacteria detected in fly samples using universal primer-multiplex PCR (Mongolian Journal of Agricultural Sciences, 2015)
Filth flies, especially house fly, Musca domestica L., not only is a nuisance pest, but also acts as an important mechanical vector for pathogenic microorganism agents, including bacteria, protozoa, worms, fungi and viruses amongst humans and animals. More than 100 pathogens are associated with the house fly and bacteria have been isolated from feces, vomits, external surfaces, and internal organs of this species (De Vos V, et al., 1998; Dragon, DC, 1995; West, 1951; Markus, 1980; Kasprzak et al, 1981; Akinboade et al., 1984; Iwasa et al., 1999).The aim of this study was to detect pathogenic bacteria from house fly by UP-M-PCR. In this study, totally 267house flies were collected and we tried to find a procedure enabling the detection of three pathogens namely, Escherichia coli, Listeria monocytogenes, Salmonella spp and employed for multiplex PCR analysis in house fly. The most common isolated bacteria were L. monocytogenes(132 cases: 49.4%) and another isolated bacteria belong to E. coli (114 case: 42.6%) and Salmonella spp (98 cases: 36.7%). The results of the current study confirm that flies are much more than a nuisance and that they pose potentially serious health risks. The epidemiologic potential of house flies to disseminate pathogenic bacteria may be greater than initially suspected.Mongolian Journal of Agricultural Sciences Vol.15(2) 2015; 27-32